Linguistic Purpose and Historical Implications of Malapropism and Code-Switching in the Philippines - Michael Laguidao Estremera (Indonesian Journal of EFL and Linguistics, 2021)
The present article underpins the affirmation that colonization does have historical, linguistic, and cultural impact. Specifically, this paper explores the social malapropism and code-switching as trails of colonization dented by the American and Spanish regimes in the Philippines. The author concludes that malapropism occurs coupled with the code-switching linguistic phenomenon. Most of the malapropism episodes transpired is a prelude to shifting from one language to another. These occurrences have veiled implications and purposes which are established by the semantic features of the discourses. Collectively, the linguistic influence handed down by the colonizers had been found to be the chief contributory factor to the preceding phenomena. Bilingualism or even multilingualism induces malapropism and code-switching occurrences inevitably. The incompetence in choosing appropriate words and the low cache of lexical terms slightly affects the preceding phenomena. Taking into account the outcomes and conclusion, teachers must be cognizant of these occurrences to be able to cope with these phenomena accordingly thereby convert such drawbacks to communication into rich opportunities for meaningful classroom tête-à-tête. To the extent that there is complete communication cycle in malapropism and code-switching discourses, these could be exploited as bridges to learn the L2. Since there has likewise been language assimilation in code-switching, such can be used as an opportunity to master the second language by guiding learners toward fluency and accuracy. Morphological and phonological awareness will symbiotically follow sooner through series of drills and philosophical practice of the language.